If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -4x = 4x + 7 Reorder the terms: -7 + -4x = 7 + 4x Solving -7 + -4x = 7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -7 + -4x + -4x = 7 + 4x + -4x Combine like terms: -4x + -4x = -8x -7 + -8x = 7 + 4x + -4x Combine like terms: 4x + -4x = 0 -7 + -8x = 7 + 0 -7 + -8x = 7 Add '7' to each side of the equation. -7 + 7 + -8x = 7 + 7 Combine like terms: -7 + 7 = 0 0 + -8x = 7 + 7 -8x = 7 + 7 Combine like terms: 7 + 7 = 14 -8x = 14 Divide each side by '-8'. x = -1.75 Simplifying x = -1.75
| 4x+5=47-2x | | 4x+5=47-2x | | 14x+2x= | | 0.2y=-1.2 | | -x+4y+z= | | 7(2x-6)-4(5x-8)=-5x | | 68-6x=3x+19 | | 5(x-1)=3-(3x+7)+(4-2x) | | 7-10x=89-24x | | 7+6x=57+x | | 7x=-84 | | 13x+29y=17 | | x+4=4x | | 6x+38=15x-70 | | 141-5x=4x+24 | | 3y-6=-15 | | 4x+83=10x+11 | | 6x+13=83-4x | | 3y-6=15 | | H+1=4h-20 | | 5(2x-1)=3(2x+5) | | 6x^2+1=5x | | n+3=7 | | x^2=8x-35 | | n+3=7n-6 | | 7-2(x-3)=-7-5(4+x)+7 | | 8x-5=2x-7 | | 0.5t+1.6=t+0.1 | | 3x^2+1=-4x | | -x+19=x+1 | | 8+2x-9x=2(x+3)-7 | | x+17=3x+1 |